2014
DOI: 10.1016/j.energy.2014.04.083
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of massive exhaust gas recirculation and Miller cycle strategies for mixing-controlled low temperature combustion in a heavy duty diesel engine

Abstract: ElsevierMolina Alcaide, SA.; Benajes Calvo, JV.; Novella Rosa, R.; Belarte Mañes, E. (2014). Evaluation of massive exhaust gas recirculation and Miller cycle strategies for mixingcontrolled low temperature combustion in a heavy duty diesel engine. Energy. (71) AbstractThe future of compression ignition engines depends on their ability for keeping their competitiveness in terms of fuel consumption compared to spark-ignition engines. In this competitive framework, the Low Temperature Combustion (LTC) concept is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…NOx reduction achieved with a Miller cycle strategy was limited primarily due to the small 347 impact on the in-cylinder flame temperature, as reported by Benajes et al [49]. The use of EGR can effectively curb NOx emissions but the fuel conversion efficiency could 352 be compromised when introducing EGR to Miller cycle operation at high engine loads.…”
Section: Test Conditionsmentioning
confidence: 99%
“…NOx reduction achieved with a Miller cycle strategy was limited primarily due to the small 347 impact on the in-cylinder flame temperature, as reported by Benajes et al [49]. The use of EGR can effectively curb NOx emissions but the fuel conversion efficiency could 352 be compromised when introducing EGR to Miller cycle operation at high engine loads.…”
Section: Test Conditionsmentioning
confidence: 99%
“…The Miller cycle has been proposed as another solution to comply with NOx regulations. This method is based on a decrease of the combustion temperatures by reducing the effective compression ratio through the air management settings [9,10]. The main disadvantage of this method is that it implies a worsening of engine performance.…”
Section: Introductionmentioning
confidence: 99%
“…In references [16,17], deeper Miller timing over 20°CA BBDC and an EGR rate which is higher than 20% were not presented, and Jesús Benajes confirmed how Miller cycle and EGR strategies are suitable for decreasing simultaneously NOx and soot emissions down to ultra-low levels, but he did not investigate the combination of these two technologies. For the Tier III emission regulation, NOx emissions still need to be further reduced if only one of the two technologies is adopted.…”
Section: Figurementioning
confidence: 99%
“…It can be concluded that the EGR system is an essential part of an engine concept in order to fulfill IMO Tier III NOx requirements, but only one Miller IVC (20°CA BBDC) was tested in his paper. In reference [17], a 1.8 l single-cylinder diesel engine was studied by Jesús Benajes by combining direct experimental data with the detailed information on the local in-cylinder conditions obtained from 3D-CFD simulations. The research was combined to compare the 10%-16% EGR and Miller (effective compression ratio = 8~14.4) strategies respectively in terms of the emissions, efficiency and the local combustion process.…”
Section: Figurementioning
confidence: 99%